This is not about you(th) - Kuryshchuk, Olya., ....- ([London] : 1 Granary, 2023)
1 Granary Issue 7 contains excerpts from interviews with over 50 senior luxury employees, the result of two years of research and more than 100 off-the-record conversations. They include design directors, heads of leather goods and accessories, senior designers, collection managers, heads of womenswear, menswear, print, flou, VIP, tailoring and outerwear, knitwear consultants, studio and fabric directors, product developers, and vice-presidents of shoes, bags, or sunglasses, who work for Versace, Dior, Jil Sander, Jacquemus, Prada, Lanvin, Fendi, Marni, Louis Vuitton, Alexander McQueen, Victoria Beckham, Burberry, The Row, Calvin Klein, Bottega Veneta, Sonia Rykiel, Margaret Howell, Phoebe Philo, Balenciaga, Loewe, AZ Factory, Balmain, Y/Project, and Oscar de La Renta, among others. Their anonymous testimonies reveal the structural problems at the heart of our industry while presenting new visions for the future. Topics include intergenerational conflict, ageism, creative management, leadership, money, salary transparency, power dynamics, motherhood, and gender equality.